DISCOVERING THE SCHOLARSHIP DIMENSION OF AHMADIYYA: Ahmadiyya’s School on Indonesian Islam’s Views - Thoriquttyas, Titis (Journal of Islamic Education, 2020)
AbstractIndonesian Islam’s ideas were clearly elaborate about the teachings of Islam which promoting the tolerant, creating Muslim society who has harmonious and respecting the minority rights, such as on Ahmadiyya’s issues. This article shows how Ahmadiyya communities are able to survive in Yogyakarta through educational institution and how the others society receive their existence peacefully. Limiting its scope on Ahmadiyya’s school namely, Yayasan PIRI (Perguruan Islam Republik Indonesia) Yogyakarta which established on 1942 and it labeled as Ahmadiyya’s school based on its history especially refers to Gerakan Ahmadiyya Indonesia. This paper drawn on the acceptability of Ahmadiyya's school around the society and its effort to negotiate their position used the Indonesian Islam ideas as the approach and the perspective. Furthermore, researcher will point out its uniqueness from the curriculum (learning materials), the educators and its learning methods in order to find the basic characteristics which it appropriate with what Indonesian Islam ideas could be contributed Keywords: Indonesian Islam, Ahmadiyya’s School, Yayasan PIRI Yogyakarta